Tomato Components and Quality Parameters. A Review - Amr, Ayed; Raie, Wesal (Jordan Journal of Agricultural Sciences, 2022)
Tomatoes (Solanum lycopersicum L.) are some of the most important vegetable foods worldwide. They are the second largest grown vegetable in both terms of production and consumption. Demand for tomatoes has been increasing recently due to their high content of nutritionally- acclaimed carotenoids, fibers, vitamins, and minerals, hence it has been the subject of numerous studies both in the laboratory and under field conditions. The quality of a tomato is determined by internal and external attributes, internal such as texture, sweetness, acidity, aroma, flavor, and nutritional value, and external which are appearance factors such as color, shape, size, and firmness. This review aims to investigate the chemical composition of tomato fruits and how they influence their quality. The findings of chemical composition (minor and major) components that were reported by many researchers are reviewed in this article.  Also, this review focuses on the effect of tomato variety on the chemical composition of this fruit, and how these components are varied during the ripening process. In addition, chemical, physical and sensory quality factors were discussed in this review.